Synthesis and optimization of membrane cascade for gas separation via mixed‐integer nonlinear programming - Aliaga‐Vicente, Alicia; Caballero, José A.; Fernández‐Torres, María J. (AIChE journal, 2017)
Currently, membrane gas separation systems enjoy widespread acceptance in industry as multistage systems are needed to achieve high recovery and high product purity simultaneously, many such configurations are possible. These designs rely on the process engineer's experience and therefore suboptimal configurations are often the result. This article proposes a systematic methodology for obtaining the optimal multistage membrane flow sheet and corresponding operating conditions. The new approach is applied to cross‐flow membrane modules that separate CO 2 from CH 4 , for which the optimization of the proposed superstructure has been achieved via a mixed‐integer nonlinear programming model, with the gas processing cost as objective function. The novelty of this work resides in the large number of possible interconnections between each membrane module, the energy recovery from the high pressure outlet stream and allowing for nonisothermal conditions. The results presented in this work comprise the optimal flow sheet and operating conditions of two case studies. © 2017 American Institute of Chemical Engineers AIChE J , 63: 1989–2006, 2017